(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Pain syndrome is a complex complecation of painful sensations of different severity, according to statistics, at least one episode of headache occurs in 70-75% of the population, and in 25-40% of cases from IT, headaches are of a permanent or recurrent character. The following main clinical forms of headaches are differentiated: migraines, tension headaches, smoky (cluster) cephalgia, chronic paroxysmal hemicrania, intracranial disorders that do not depend on stroke and blood vessels, consumption of certain substances, pain associated with infection and metabolic disorders. There are also pains caused by excessive medication intake, expressed in drug dependence. This pathology, which in most cases is resistant to medication, often causes patients to lose their working capacity and sometimes disability.